Food price inflation and children's schooling - Michael Grimm (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
I analyze the impact of food price inflation on parental decisions to send their children to school. Moreover, I use the fact that food crop farmers and cotton farmers were exposed differently to that shock to estimate the income elasticity of school enrolment. The results suggest that the shock-induced loss in purchasing power had an immediate effect on enrolment rates. Instrumental variable estimates show that the effect of household income on children's school enrolment is much larger than a simple OLS regression would suggest. Hence, policies to expand education in Sub-Saharan Africa, should not neglect the demand side.
Keywords: I21; O12; Q12; 330; Education; household income; inflation; aggregate shocks; Africa; Nahrungsmittelpreis; Schock; Kinder; Bildungsverhalten; Schüler; Haushaltseinkommen; Schock; Afrika südlich der Sahara